THE EFFECT OF BREAST MILK TOWARD CHILDREN’S GROWTH: A SYSTEMATIC REVIEW - Anggraini, Dewi (LIFE: International Journal of Health and Life-Sciences, 2017)
Exclusive breastfeeding is breast milk consumption as early as can after the birth/delivery. The breast milk is given without schedule. The baby also doesn’t get any others food, include plain water until the age of 6 months. Many researcher have shown that breastfeeding is really important to the growth of a child. The breastfeeding will be able to decrease the number of stunting problem and obesity on children. The purposes’ of the research is to give the right information about breastfeeding exclusively in order to improve the quality growth of the children. The method of the research is systematic review by searching on some database such as: Google Scholar ,EBSCO ,and Pro-Quest. The result of this systematic review shown that in many countries breastfeeding exclusively since 0-6 months is really important for the growth of children. From many characteristics, we found that breastfeeding exclusively in the age of 0 to 6 month has a significant impact to the growth of the children.